Does Discrimination Explain High Risk of Depression among High-Income African American Men? - Shervin Assari; Maryam Moghani Lankarani; Cleopatra Howard Caldwell (Behavioral Sciences, 2018)
Background: Higher socioeconomic status is known to decrease the risk for poor mental health overall. However, African American males of higher socioeconomic status (SES) are at an increased risk for having a major depressive episode (MDE). It is not known whether perceived discrimination (PD) explains this risk. The current study used nationally representative data to explore the role of PD in explaining the association between high-SES and having MDE among African American men. Methods: The National Survey of American Life (NSAL), 2003, included 4461 American adults including 1271 African American men. SES indicators (i.e., household income, educational attainment, employment status, and marital status) were the independent variables. 12-month MDE measured using the Composite International Diagnostic Interview (CIDI) was the outcome. Age, gender, and region were the covariates. PD was the potential mediator. For data analysis, we used logistic regression. Results: Among African American men, household income was positively associated with odds of 12-month MDE. The positive association between household income and odds of MDE remained unchanged after adding PD to the model, suggesting that PD may not explain why high-income African American men are at a higher risk of MDE. Conclusions: Perceived discrimination does not explain the increased risk for depression among African American males of higher SES. Future research should explore the role of other potential mechanisms such as stress, coping, social isolation, and/or negative social interaction that may increase psychological costs of upward social mobility for African American males.